Arterial blood pressure in schoolchildren, who were born after caesarian section - S. V. Popov; T. Yu. Loboda; O. I. Smiyan; E. K. Redko; I. E. Zaitsev (Zaporožskij Medicinskij Žurnal)
The aim of the study was to determine the blood pressure characteristics of school-age children, who were born by caesarean section.